The deformation characteristics of buried HDPE transfer lines in trenches under the effect of temperature - Polat, Necmettin; Erenson, Can; Terzi, Niyazi Uğur (Revista de la Construcción. Journal of Construction, 2021)
<span style="font-size: 10.0pt; line-height: 107%; font-family: 'Times New Roman',serif; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Today, the use of high-density polyethylene (HDPE) transfer lines is increasing day by day for drinking water, wastewater, sewerage networks, rainwater drainage lines, water transport structures, and natural energy sources, etc. In this study, flexible HDPE pipes were embedded in a trench to expose them to variable relative density and different thermal conditions so that the resulting deformation behavior could be investigated. Displacements and elastic strain values in the crown and spring line regions were measured. The main aim of this research was to determine the behavior of HDPE pipes under temperature effects within the framework of geotechnical principles to reflect real field conditions. As a result, pipes subject to vertical loading were tested under different relative density and thermal conditions. In the experiments carried out in a silica sandy trench, the deformations increased due to an increase in relative density. The maximum displacements and bending moment values were obtained at 50°C, which was the maximum thermal condition applied. An increase in temperature increased the deformation values due to the resulting decrease in the modulus of elasticity.